Assessment of In-Situ Gelling Microemulsion Systems upon Temperature and Dilution Condition for Corneal Delivery of Bevacizumab - Elena Peira; Giulia Chindamo; Daniela Chirio; Simona Sapino; Simonetta Oliaro-Bosso; Erica Rebba; Pavlo Ivanchenko; Marina Gallarate (MDPI AG, 2021)
Bevacizumab (BVZ), a recombinant humanized monoclonal antibody, has recently been proposed as a topical application in the treatment of anterior segment neovascularization; however, as there are some disadvantages in the administration of common eye-drops, ophthalmic topical drug delivery systems are under study to improve the precorneal residence time, reducing the frequency of administration. In this work, oil-in-water and water-in-oil BVZ-loaded microemulsions are developed, able to increase their viscosity, either by the formation of a liquid-crystalline structure upon aqueous dilution, thanks to the presence of Epikuron® 200 and polysorbate 80, or by body-temperature-induced jellification for the presence of Pluronic® F127 aqueous solution as an external phase. In oil-in-water microemulsion, hydrophobic ion pairs of BVZ were also prepared, and their incorporation was determined by release studies. Microemulsions were characterized for rheological behavior, corneal opacity, in vitro corneal permeation, and adhesion properties. The studied microemulsions were able to incorporate BVZ (from 1.25 to 1.6 mg/mL), which maintained dose-dependent activity on retinal pigment epithelial ARPE-19 cell lines. BVZ loaded in microemulsions permeated the excised cornea easier (0.76-1.56% BVZ diffused, 4-20% BVZ accumulated) than BVZ commercial solution (0.4% BVZ diffused, 5% accumulated) and only a mild irritation effect on the excised cornea was observed. The good adhesion properties as well the increased viscosity after application, under conditions that mimic the corneal environment (from 1 × 103 to more than 100 × 103 mPa·s), might prolong precorneal residence time, proving these systems could be excellent topical BVZ release systems.